Diverse Leadership and Firm Success: The Role of Top Management Socialisation (Marketing i Menedžment Innovacij)
Although executive teams play a significant role in organisational performance, it is necessary to conduct a comprehensive exploration of the distinct effects of the characteristics of different team members on firm outcomes. Drawing upon multiple theories applied in top management team (TMT) research, the objective of this article is to determine the effects of factors such as age, gender, and cultural background on firm performance. Moreover, our research reinforces the connection between diversity and corporate outcomes by incorporating TMT socialisation as a moderator shaping the interplay between team traits and performance. We use the quantitative method, compiling a dataset of 661 publicly listed IT-related corporations in the U.S. that were operational in 2016. Following an initial assessment of the dataset, we excluded 153 companies with fewer than three members on the board of directors or a cultural diversity score of zero and a further 66 that reported a return on assets below our lower limit. A regression analysis was then conducted on the remaining 442 companies via performance data from the OSIRIS global database. Initially, TMT gender division emerges as the primary factor that positively impacts firm performance, closely followed by age and cultural diversity. This study extends the literature on the relationship between top management and organisational outcomes. We further find that socialisation plays a crucial moderating role in the associations between TMT gender diversity, age diversity, and firm performance. The study offers actionable guidance for managers and policymakers in identifying key priorities related to executive characteristics by addressing varying perspectives stemming from diverse age groups, genders, and nationalities within a team. While most studies concentrate on identifying key drivers and their impacts, our current research reinforces the connection between diversity and firm performance by incorporating team socialisation, and we find that the benefits of diversity could be maximised through effective collaboration among managers, with minimal conflict, thereby suggesting how organisations can better shape the roles of board members’ characteristics.